Porous carbon material, silicon-carbon composite material and preparation method and application thereof
Porous carbon materials are prepared by combining zinc chloride with nitric acid, which solves the problems of low-grade, poor strength and incomplete removal of impurities in the prior art, and has achieved porous carbon materials with high specific surface area, strength and electrochemical properties, reducing production costs.
Patent Information
- Application Number
- CN202411846658.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-12-13
AI Technical Summary
In the prior art, the production of porous carbon materials with activated zinc chloride has defects such as low strength, poor strength, and incomplete removal of impurities, resulting in unsatisfactory battery rate performance, first effect, etc. of silicon-carbon composite materials, and high production costs.
The preparation of porous carbon materials is carried out by combining zinc chloride and nitric acid. Through heat treatment, acid washing and gas activation, the specific surface area, strength and yield of porous carbon materials are improved, and the impurity content is reduced.
The obtained porous carbon material has a high specific surface area, low impurity content and high strength. The silicon-carbon composite material used to prepare shows excellent electrochemical performance in lithium-ion batteries, with significantly improved first-effect and cycling performance, and greatly reduced production costs.
Smart Images

Figure BDA0005189495770000111 
Figure BDA0005189495770000121 
Figure BDA0005189495770000131
Abstract
Description
Technical Field
[0001] The invention relates to a porous carbon material, a silicon-carbon composite material, and a preparation method and application thereof. Background Art
[0002] Silicon-carbon composites have attracted widespread attention due to their extremely high energy density and are widely used in the field of consumer batteries. The general preparation process of silicon-carbon composites includes precursor preparation → precursor carbonization → precursor activation (porous carbon) → silane deposition → carbon source coating, etc. Among them, the influence of porous carbon on silicon-carbon composites is crucial. The main reason is that porous carbon materials, as carriers of silicon-carbon composites, have good void distribution and conductivity that affect the rate, expansion, and strength of silicon-carbon composites. Because of the difficulty in preparing ideal porous carbon, the low yield of porous carbon after carbonization and activation, and the small amount of porous carbon remaining after multiple processes, the price of porous carbon can reach 400,000 RMB / t. Moreover, it is usually necessary to use CO2, alkali, water vapor and other methods. These activation methods are mainly based on etching, which is the main reason for the low yield of porous carbon. In addition, due to the activation method, various functional groups are easily generated in the porous carbon, affecting the rate performance, initial efficiency and strength of silicon-carbon composite materials based on porous carbon. In addition, because the hard carbon material prepared based on the precursor has a very large tap density and lacks the necessary gaps on its surface, this leads to extremely low efficiency and high cost in the method of active activation by gas adsorption. If the waste gas cannot be recovered, it will be a huge waste of resources, etc.
[0003] Porous carbon materials activated by zinc chloride have a very high yield. Moreover, based on the activation principle, the porous carbon formed has more mesopores in the shape of gaps. At the same time, the carbon formed has a layered structure, the degree of graphitization increases, and the conductivity is improved to a certain extent. However, the porous carbon materials activated by zinc chloride are often lower than the surface, usually only reaching 1500m 2 / g, which is obviously not conducive to the deposition of silane. In addition, the layered structure in the porous carbon formed by it is extremely unfavorable for strength. In addition, the zinc chloride activator is a heavy metal salt with a narrow voltage window range. Within the voltage window range of lithium-ion batteries, if the porous carbon material activated by zinc chloride is not thoroughly cleaned, it will cause extremely important hidden dangers during the repeated charging and discharging of the battery, including the impact on performance and safety. At the least, the life span is greatly reduced, the rate performance is reduced, and at the worst, the battery short circuit is caused, directly scrapped, and even fire is caused. Summary of the invention
[0004] The present invention is to solve the defects of low specific surface area, poor strength, incomplete impurity removal, etc. in the porous carbon material prepared by zinc chloride activation in the prior art, and further based on the problem that the battery rate performance and first effect of the porous carbon material prepared into silicon-carbon composite material are not ideal, a porous carbon material, a silicon-carbon composite material and its preparation method and application are proposed. The porous carbon material obtained by the preparation method of the present invention has low impurity content, high specific surface area and high strength. The silicon-carbon composite material prepared by the porous carbon material has excellent electrochemical properties when used in lithium-ion batteries; and the preparation method of the present invention greatly improves the yield of the porous carbon material and does not require tempering treatment, which greatly reduces the production cost of the porous carbon material.
[0005] The present invention adopts the following technical solutions to solve the above technical problems:
[0006] The present invention provides a method for preparing a porous carbon material, which comprises the following steps:
[0007] S1, subjecting a mixture of a carbon material and zinc chloride to heat treatment and acid washing to obtain a first precursor;
[0008] S2. Mix the first precursor, nitric acid and polar solvent, soak and dry.
[0009] In the present invention, in step S1, the mass ratio of the carbon material to the zinc chloride is preferably 1:(1-10), more preferably 1:(3-5), for example 1:3.
[0010] In step S1, the temperature of the heat treatment is preferably 500-800°C, for example 600°C.
[0011] In step S1, the heating rate of the heat treatment is preferably 1-10°C / min, for example 2°C / min. The heating rate means the heating rate during the process of increasing the temperature from room temperature to the heat treatment temperature.
[0012] In step S1, the heat treatment can be performed in a conventional heating device in the art, such as a rotary furnace, a fluidized bed, a push plate kiln, a tube furnace, a muffle furnace, a vacuum furnace or a microwave oven. In a specific embodiment, the heat treatment is performed in a rotary furnace, wherein, preferably, the rotation speed of the rotary furnace is 5-20 r / min, for example, 10 r / min.
[0013] In step S1, the heat treatment can be performed in an inert atmosphere. Preferably, the inert atmosphere is nitrogen, helium or argon. Preferably, the inert atmosphere has a gas supply rate of 1-10 L·kg 1 min -1 , for example 2L·kg 1 min -1.
[0014] In step S1, the heat treatment holding time may be 1-5 hours, for example, 3 hours.
[0015] In step S1, the acid washing can be performed with a conventional acid. The concentration of the acid is preferably 0.1-5 M, for example 1 M. The acid washing is preferably performed with hydrochloric acid.
[0016] In step S1, after the acid washing, the waste liquid may be recovered and dried.
[0017] In step S1, the particle size D of the carbon material is 50 Preferably, it is 5-10 μm, for example, 8.1 μm.
[0018] In step S1, the water content of the first precursor may be 20%-80%, for example, 50%, wherein the water content refers to the percentage of the mass of water in the first precursor to the total mass of the first precursor.
[0019] In step S2, the pH value of the mixture slurry of the first precursor, nitric acid and polar solvent is 2-6, for example, 2.
[0020] In step S2, the nitric acid is preferably dilute nitric acid.
[0021] In step S2, the polar solvent may be one or more of N-methylpyrrolidone (NMP), water, acetone, ethanol, chloroform, ether, acetic acid, acetonitrile, isopropanol and methanol, for example, N-methylpyrrolidone.
[0022] In step S2, the amount of the polar solvent used may be 0.1%-5%, where the percentage is the mass percentage of the polar solvent in the mixture slurry of the first precursor, nitric acid and the polar solvent.
[0023] In step S2, during the soaking process, zinc chloride reacts with nitric acid: ZnCl2+HNO3→Zn(NO3)2+HCl, and HCl escapes in the form of gas.
[0024] In step S2, the soaking may be performed at room temperature.
[0025] In step S2, the soaking time is preferably 5-20 hours, preferably 10 hours.
[0026] In step S2, the soaking pressure is preferably 10-50 kPa, for example, 10 kPa. The soaking pressure refers to the pressure in the container during soaking, which can be achieved by vacuuming. The purpose of soaking under conditions below normal pressure is to reduce the tension of bubbles (HCl gas) in the pores, promote the reaction of nitric acid with ZnCl2 in the material, and continuously make the reaction ZnCl2+HNO3→Zn(NO3)2+HCl proceed to the right.
[0027] In step S2, the drying is performed in conventional equipment in the art, such as a vacuum drying oven, a rotary evaporator, a forced air drying oven or a double cone drying oven.
[0028] In step S2, the drying is preferably vacuum drying.
[0029] Preferably, the vacuum drying pressure is 10-50 kPa.
[0030] Preferably, the vacuum drying time is 5-20 hours, such as 10 hours.
[0031] Preferably, the vacuum drying temperature is 80-150°C, for example 100°C.
[0032] In the present invention, preferably, the product obtained in step S2 is recorded as the second precursor, and after step S2, the following steps are further included:
[0033] Step S3, performing gas activation treatment on the second precursor.
[0034] In step S3, the gas source for gas activation is preferably CO2.
[0035] In step S3, the gas activation time may be 1-10 hours.
[0036] In step S3, the gas activation gas supply rate can be 0.5-5L·kg 1 min -1 , preferably 2L·kg 1 min -1 .
[0037] In step S3, the temperature of the gas activation may be 500-800°C, preferably 500-600°C, for example 600°C.
[0038] In the present invention, preferably, before step S1, the following steps are further included:
[0039] Step S0: carbonizing the mixture containing the carbon source to obtain a carbon material.
[0040] In step S0, the carbon source comprises one or more of resin, sucrose, glucose, fructose, starch, cellulose, triglyceride, fatty acid, hemicellulose, lignin and asphalt. Wherein, the carbon source is preferably resin, more preferably phenolic resin.
[0041] In step S0, the carbonization may be performed by a staged heat treatment. Preferably, the carbonization includes the following stages:
[0042] The first stage: heating to 50-300℃ at a heating rate of 0.1-20℃ / min, keeping temperature for 5-600min;
[0043] The second stage: heating to 300-1000°C at a heating rate of 0.1-20°C / min, and keeping the temperature for 5-1200min.
[0044] In a specific embodiment, the carbonization comprises the following steps: firstly heating the temperature at a heating rate of 4°C / min for 50min to 200°C and keeping the temperature for 1h; then heating the temperature at a heating rate of 4°C / min for 113min to 652°C and keeping the temperature for 1h.
[0045] In step S0, the carbonization is carried out under an inert atmosphere, and the inert atmosphere is one or more of nitrogen, helium and argon. Preferably, the inert gas supply rate is 1-5 L·kg -1 min -1 .
[0046] In step S0, the mixture may further include a curing agent and a solvent.
[0047] Preferably, the curing agent is one or more of urotropine, ethylenediamine, hexamethylenediamine, diethylenetriamine, triethylenetetramine, diethylaminopropylamine, hexamethylenetetramine, aniline, p-toluenesulfonic acid, formaldehyde, benzenesulfonyl chloride, p-toluenesulfonyl chloride, ethyl sulfate, petroleum sulfonic acid, dodecylbenzenesulfonic acid, polyoxymethylene, maleic anhydride, phthalic anhydride, isocyanate, pyridine, benzoyl peroxide, cumene hydroperoxide, tert-butyl hydroperoxide and cyclohexanone peroxide, such as urotropine.
[0048] Preferably, the solvent is one or more of water, N-methylpyrrolidone, water, acetone, ethanol, chloroform, ether, acetic acid, acetonitrile, isopropanol and methanol.
[0049] Preferably, the ratio of the total mass of the curing agent and the solvent to the mass of the carbon source is (0.001-5):1.
[0050] In step S0, the preparation of the mixture may include mixing the components.
[0051] The mixing can be carried out in conventional equipment in the art, such as a high-speed dispersing homogenizer, a planetary dispersing machine, an ultrasonic cell pulverizer or an ultrasonic cleaning machine.
[0052] The mixing speed may be 1000-5000 r / min, for example, 2000 r / min.
[0053] The mixing time may be 1-600 min, for example 60 min.
[0054] In step S0, a drying process is also included before the carbonization.
[0055] The drying method may be a conventional method in the art, such as spray drying, rotary evaporation, spray drying or vacuum granulation.
[0056] In some preferred embodiments, the drying method is spray drying.
[0057] The spray drying temperature may be 50-200°C, for example 130°C.
[0058] The particle diameter of the spray-dried material may be 5-20 μm, for example 8 μm.
[0059] The present invention provides a porous carbon material prepared by adopting the method for preparing the porous carbon material.
[0060] In the present invention, preferably, the specific surface area of the porous carbon material is 1500-2000m 2 / g, for example, 1535m 2 / g、1639m 2 / g, 1867m 2 / g、1693m 2 / g, 1832m 2 / g or 1935m 2 / g.
[0061] Preferably, the micropore specific surface area ratio of the porous carbon material is greater than 90%, wherein the micropore specific surface area ratio refers to the percentage of the specific surface area of the micropores to the total specific surface area of the porous carbon material.
[0062] Preferably, the mesopore specific surface area of the porous carbon material is less than 10%, for example, 7.0%, 7.7%, 7.9%, 8.0%, 8.1%, 8.4%, 8.8%, 9.3% or 9.8%, wherein the mesopore specific surface area refers to the percentage of the specific surface area of the mesopores to the total specific surface area of the porous carbon material.
[0063] Preferably, the total pore volume of the porous carbon material is 0.6-1.2 cm3 / g, for example, 1.12 cm 3 / g.
[0064] The present invention provides a method for preparing a silicon-carbon composite material, which comprises the following steps (referred to as step S4): sequentially performing silicon deposition and carbon coating on the porous carbon material.
[0065] In step S4, the silicon source for silicon deposition preferably includes silane (general formula: Si n H 2n+2 ), the silane may be monosilane (SiH4), disilane (Si2H6), trisilane (Si3H8) and tetrasilane (Si4H 10 )
[0066] In step S4, the ventilation volume of the silicon source for silicon deposition can be 0.1-10 L·kg -1 min -1 , for example 0.5L·kg -1 min -1 .
[0067] In step S4, preferably, during the silicon deposition process, a silicon source and a carrier gas are introduced simultaneously, wherein the volume ratio of the silicon source to the carrier gas is 1:(2-6), for example, 1:4.
[0068] In step S4, the temperature of silicon deposition may be 400-800°C, for example, 550°C.
[0069] In step S4, the silicon deposition time may be 3-16 hours, for example, 8 hours.
[0070] In step S4, the carbon coating can be performed by conventional methods in the art.
[0071] In some preferred embodiments, the carbon coating is performed by vapor deposition.
[0072] Among them, the carbon-coated carbon source may include one or more of alkynes (such as acetylene), alkanes, olefins, aromatic compounds (such as one or more of anthracene, naphthalene and lignin) and carbohydrates (such as one or more of glucose, cellulose and hemicellulose).
[0073] Wherein, the ventilation volume of the carbon source can be 0.1-10L·kg -1 min -1 , for example 2L·kg -1 min -1 The carbon coating temperature may be 300-1000°C, for example 600°C.
[0074] The carbon coating time may be 60-1200 min, for example 600 min.
[0075] The present invention provides a silicon-carbon composite material, which is prepared by adopting the preparation method of the silicon-carbon composite material.
[0076] In the present invention, preferably, the silicon-carbon composite material comprises, from inside to outside, a porous carbon skeleton, a silicon deposition layer and a carbon coating layer; wherein the silicon deposition layer is located on the pore walls in the porous carbon skeleton.
[0077] The silicon-carbon composite material is used as an electrode material in a battery.
[0078] Wherein, the electrode material is preferably a negative electrode material.
[0079] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.
[0080] The reagents and raw materials used in the present invention are commercially available.
[0081] The positive and progressive effects of the present invention are:
[0082] 1. The present invention uses zinc chloride and nitric acid to improve the yield of porous carbon materials (from less than 20% in the prior art to more than 45%), greatly reducing the manufacturing cost of porous carbon. At the same time, the zinc content inside the porous carbon is reduced to the maximum extent, so that the impurity content is reduced to less than 170ppm.
[0083] 2. In the preferred embodiment, further activation with CO2 can further improve the yield of porous carbon materials. The CO2 ventilation volume required by this method is only 0.5-5L·kg 1 min -1 The ventilation time is only 1-10 hours, which is much lower than the amount of CO2 used in the prior art, and can further reduce production costs. In addition, the preparation method of the porous carbon material of the present invention can minimize the impact on the equipment and promote the development of large-scale mass production technology.
[0084] 3. The porous carbon material of the present invention has low impurity content, high specific surface area and high strength. The silicon-carbon composite material prepared by using the porous carbon material has excellent electrochemical properties when used in lithium-ion batteries, especially the first effect (the first effect can reach more than 83%) and cycle performance (the 1C cycle failure parameter at 25°C can reach more than 55 cycles). DETAILED DESCRIPTION
[0085] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.
[0086] Phenolic resin was purchased from Hubei Hengye Technology Co., Ltd., model 2135.
[0087] Example 1
[0088] S0. Preparation of carbon materials:
[0089] (1) 1 kg of phenolic resin, 2 kg of alcohol, and 60 g of hexamethylenetetramine (HMT) were mixed by a high-speed homogenizer at a speed of 2000 r / min for 60 min. The mixture was then spray-dried at 130° C. until the particle diameter was 8 μm.
[0090] (2) The spray-dried powder was placed in a rotary furnace with a rotation speed of 10 r / min and a nitrogen atmosphere gas supply rate of 1 L·kg -1 min -1 , carbonization is carried out: the first stage: heating at 4°C / min for 50min, then heating to 200°C and keeping it for 1h, the main purpose of which is to make the phenolic resin cross-linked; the second stage: heating at 4°C / min for 113min, then heating to 652°C and keeping it for 1h; the particle size of the obtained carbon material is D50=8.1μm.
[0091] S1. Activation of carbon material: First, 10 kg of carbon material was mixed with 30 kg of zinc chloride, and the rotation speed of the rotary furnace was adjusted to 10 r / min, and the nitrogen supply rate was 2 L·kg -1 min -1 The heating rate in the furnace is 2°C / min. After the temperature reaches 600°C, it is kept for 3 hours, and then the temperature in the furnace is cooled to room temperature. Secondly, the material is taken out and washed with hydrochloric acid (concentration is 1M) to obtain the first precursor (water content is 50%), and the waste liquid is recovered and dried.
[0092] S2. Add 35 kg of the first precursor to 7 kg of dilute nitric acid, and add NMP to obtain a mixture slurry. The pH of the mixture slurry is 2, and the mass fraction of NMP in the mixture slurry is 5%. Soak at room temperature for 10 hours, and continuously pump the pressure to 10 kPa. Then filter the material, place the filtered material in a vacuum drying oven, keep the pressure inside the vacuum drying oven at 10k, keep the temperature at 100 ° C, and dry for 10 hours to obtain a second precursor.
[0093] S3, then transferred to the rotary furnace for activation under CO2 atmosphere, with a gas supply rate of 2L·kg 1 min-1 , activation time is 1h, activation temperature is 600℃, and porous carbon material is obtained.
[0094] S4. Preparation of silicon-carbon composite materials:
[0095] The atmosphere was switched to monosilane containing a carrier gas (20% monosilane and 80% argon by volume) and the deposition was carried out at 550 °C for 8 h with a ventilation volume of 0.5 L kg -1 min -1 .
[0096] Then acetylene was introduced, and the ventilation rate of acetylene was 2L·kg -1 min -1 , and maintained at 600°C for 600min to obtain a silicon-carbon composite material.
[0097] Example 2
[0098] The difference from Example 1 is that the CO2 activation time in step S3 is 3 hours; the other conditions are the same as those in Example 1.
[0099] Example 3
[0100] The difference from Example 1 is that the CO2 activation time in step S3 is 7 hours; the other conditions are the same as those in Example 1.
[0101] Example 4
[0102] The difference from Example 1 is that in step S1, the mass ratio of zinc chloride to carbon material is 1:4, that is, 10 kg of carbon material and 40 kg of zinc chloride are used; the other conditions are the same as those in Example 1.
[0103] Example 5
[0104] The difference from Example 4 is that the CO2 activation time in step S3 is 3 hours; the other conditions are the same as those in Example 4.
[0105] Example 6
[0106] The difference from Example 4 is that the CO2 activation time in step S3 is 7 hours; the other conditions are the same as those in Example 4.
[0107] Example 7
[0108] The difference from Example 1 is that in step S1, the mass ratio of zinc chloride to carbon material is 1:5, that is, 10 kg of carbon material and 50 kg of zinc chloride are used; the other conditions are the same as those in Example 1.
[0109] Example 8
[0110] The difference from Example 7 is that the CO2 activation time in step S3 is 3 hours; the other conditions are the same as those in Example 7.
[0111] Example 9
[0112] The difference from Example 7 is that the CO2 activation time in step S3 is 7 hours; the other conditions are the same as those in Example 7.
[0113] Comparative Example 1
[0114] In Comparative Example 1, zinc chloride is not used for pore formation, that is, steps S1 and S2 are not performed, and the carbon material obtained in step S0 is directly activated by CO2, and the specific operation is as follows: the carbon material is transferred to a rotary furnace for activation under a CO2 atmosphere for 7 hours, and the activation temperature is 600° C. Then, silicon deposition and carbon coating are performed according to step S4 of Example 1.
[0115] Comparative Example 2
[0116] The difference from Comparative Example 1 is that the activation time under CO2 atmosphere is 8 h, and the other conditions are the same as Comparative Example 1.
[0117] Comparative Example 3
[0118] The difference from Comparative Example 1 is that the activation time under CO2 atmosphere is 9 h, and the other conditions are the same as Comparative Example 1.
[0119] Comparative Example 4
[0120] The difference from Comparative Example 1 is that the activation time under CO2 atmosphere is 10 h, and the other conditions are the same as Comparative Example 1.
[0121] Comparative Example 5
[0122] The difference from Comparative Example 1 is that the activation time under CO2 atmosphere is 11 h, and the other conditions are the same as Comparative Example 1.
[0123] Comparative Example 6
[0124] The difference between this comparative example and Example 1 is that gas activation is not performed, that is, step S3 is not performed, and the other conditions are the same as those of Example 1.
[0125] Comparative Example 7
[0126] The difference from Comparative Example 1 is that the activation time under CO2 atmosphere is 3 h, and the other conditions are the same as Comparative Example 1.
[0127] Comparative Example 8
[0128] The difference between this comparative example and Example 6 is that the process of treating with dilute nitric acid in step S2 is not performed, and the other conditions are the same as those in Example 6.
[0129] Effect Example 1
[0130] 1. Particle size test: Laser particle size analyzer is used to test the D 50 Particle size, tested at 0Mpa, 5Mpa, 10Mpa, 15Mpa and 20Mpa respectively.
[0131] 2. Test of element content: The carbon content and sulfur content of each embodiment and comparative example were measured by a sulfur-carbon instrument, and the silicon content was obtained by calculation, that is, silicon content (%) = 100 - carbon content (%) - sulfur content (%).
[0132] 3. Porous carbon yield: The calculation method is to divide the mass of porous carbon produced by the amount of carbon material input.
[0133] 4. Test of lithium insertion expansion: It can be calculated by the following formula: (pole thickness after saturated lithium insertion - copper foil thickness) / (pole thickness without lithium insertion - copper foil thickness).
[0134] 5. Specific surface area test: carried out using Micromeritics ASAP2020.
[0135] 6. Test for impurity metal ion content: Use microwave digestion instrument, aqua regia, HF and other auxiliary detection, and liquid chromatography to detect the impurity metal ion content in the material.
[0136] According to the above test method, Examples 1-9 and Comparative Examples 1-8 were tested. The test results are shown in Table 1 and Table 2.
[0137] Table 1
[0138]
[0139]
[0140] Comparative Examples 1-5 and Comparative Example 7 are silicon-carbon composite materials prepared using the traditional CO2 activation method, while Examples 1-9 are silicon-carbon composite materials prepared using zinc chloride activation. As can be seen from the table, the greatest advantage of the method based on the coordinated activation of ZnCl2 and CO2 is that the yield of porous carbon is greatly improved and the mesopore specific surface area is comparable to that of the silicon-carbon composite material obtained by carbon dioxide activation for 11 hours. This is mainly related to the activation method of zinc chloride and the subsequent treatment with dilute nitric acid. Traditional porous carbon often uses chemical etching. Most of the carbon material overflows from the activated rotary kiln in the form of gas. The activation method of zinc chloride allows the carbonized carbon material to continue to grow around the zinc chloride molecules, and many mesopores are also produced. This allows the voids inside the porous carbon to be fully opened before further activation with CO2, greatly shortening the etching time, and also reducing the huge loss caused by opening the main channel and further deepening the etching process when preparing porous carbon. This method fully utilizes the advantages of ZnCl2, so that the specific surface area of porous carbon can reach 2000m 2 / g or above.
[0141] The yield of porous carbon in Examples 1-3 shows a decreasing trend, which may be mainly due to the insufficient amount of zinc chloride. Some pores are opened by zinc chloride and then etched away by carbon dioxide. However, it can be seen from Examples 4-9 that when the amount of zinc chloride added is within an appropriate range, there is a large numerical difference between carbon dioxide activation for 1 hour and 3 hours, while the difference between 3 hours and 7 hours is smaller. This is mainly because the etching is basically completed at 3 hours, and the porous carbon inside lacks relevant active sites that can adsorb CO2 molecules, so that the development of pores is no longer obvious.
[0142] It can be seen from Comparative Examples 1-5 and Comparative Example 7 that the longer the CO2 activation time, the larger the specific surface area of the obtained silicon-carbon composite material, the larger the mesopore specific surface area, the more silicon content of the obtained silicon-carbon composite material, but the yield of the porous carbon material will be lower. Among them, the lithium insertion expansion amounts of Comparative Examples 1-5 and Comparative Example 7 are almost the same, which is due to the expansion effect of the mesopores.
[0143] Compared with Examples 1-9, Comparative Example 6 has less micropores (smaller specific surface area) and therefore less silicon content, and the micropore development is not ideal.
[0144] Compared with Examples 1-9, Comparative Example 7 has a lower silicon content and is closer to the performance of hard carbon, so it has a better expansion reduction effect.
[0145] Compared with Example 6, Comparative Example 8 is a sample that is not washed with dilute nitric acid in step S2, and the silicon content is slightly reduced. This may be because impurities affect the development of micropores but not mesopores. Therefore, the lithium insertion expansion amount is lower than that of Example 6.
[0146] Table 2
[0147]
[0148] Compared with Comparative Example 8, Examples 1-9 further removed the generated Zn(NO3)2 under vacuum heating conditions, greatly reducing the Zn 2+ The residue makes it possible to use the porous carbon materials prepared by the zinc chloride activation process in the field of battery applications.
[0149] It can be seen from Examples 7-9 that when the amount of zinc chloride used reaches 5 times that of the porous carbon material, the increase in the proportion of mesopores therein can easily lead to a significant change in the particle size of the material under lower pressure, resulting in a decrease in the overall strength of the material.
[0150] In addition, when the mesopore ratio is larger, the lithium expansion of the silicon-carbon composite material decreases. This is mainly because the mesopores in the material can alleviate the expansion, but it will also reduce the mechanical strength of the material. It can be seen from the above table that the silicon-carbon composite materials obtained in Examples 1-9 of the present application achieve a balance between relieving volume expansion and pressure resistance.
[0151] Effect Example 2
[0152] 1. Preparation of button batteries
[0153] Preparation of negative electrode slurry and pole piece: 100g of CMC, PAA, SBR, SP, CNTs and silicon-carbon composite material with a mass ratio of 0.5:2.5:1:0.1:0.1:95.8 were added to CMC, silicon-carbon composite material, SP and CNTs in sequence, and then dispersed for 3 hours with a planetary disperser at a rotation speed of 300r / min and a revolution of 1000r / min. Then, 80% of the deionized water required for a solid content of 40% was injected at one time, and dispersed for 1 hour at a rotation speed of 500r / min and a revolution of 600r / min. PAA was added and dispersed for 1 hour at a rotation speed of 500r / min and a revolution of 500r / min. The remaining 20% of deionized water was injected, and finally SBR was added and dispersed for 1 hour at a rotation speed of 300r / min and a revolution of 300r / min. The coated current collector uses 8μm thick copper foil, double-sided coating, the coated side faces the negative electrode of the button battery, and the single-sided coating of active material is about 40μm thick, with a compaction density of 1.7g / cm 3 (The test method for compaction density is: punch the electrode into a unit circle, test the weight, subtract the weight of the copper foil, and divide it by the thickness to obtain the compaction density), wherein the coating speed is 40cm / S, the baking temperature is 80°C, and the drying time is 400s.
[0154] Preparation of electrolyte: By mass percentage, the electrolyte composition is: EC 10%, PC 15%, DEC 20%, PP 30%, LiPF6 15%, FEC 6%, PS 2.5% and LiODFB 1.5%.
[0155] Half-cell assembly: The positive electrode uses the above silicon-carbon composite material, the negative electrode uses a lithium sheet, and 0.5g of the above electrolyte is assembled into a CR2032 button battery, and the voltage serial port uses 0-1.5V. The entire battery is assembled in a glove box to avoid contact with air.
[0156] 2. Electrochemical test
[0157] Follow the steps below to test each silicon-carbon composite assembled battery.
[0158] (1) First efficiency test:
[0159] First, assemble a CR2032 button battery, and then use constant voltage discharge method, discharge it at 0.1V / h to 0.000V, then charge it at 0.1 / h to 1.5V, record the charge and discharge capacity, and calculate the initial efficiency as the lithium desorption capacity / lithium insertion capacity.
[0160] (2) 0.1C 0.8V gram capacity test:
[0161] First, assemble a CR2032 button battery, and then use constant voltage discharge method, discharge to 0.000v at 0.1V / h, charge to 0.8V at 0.1v / h, record the charging capacity of 0.5C, reassemble a CR2032 button battery, and perform constant current charge and discharge test to record the charging capacity of 0.1C, discharge to 0v and then charge to 0.8v. After obtaining the capacity, use the capacity / mass of active matter in the electrode method to obtain the gram capacity of 0.1C 0.8V.
[0162] (3) Cycle failure parameter test:
[0163] ①1C 0.8V cycle failure parameters (measured at 25℃ and 45℃ respectively):
[0164] The above button battery was discharged at a constant voltage of 0.1V / h to 0.000V, and then charged at 0.1V / h to 0.8V, and the charging capacity was recorded. A button battery was reassembled and a constant current charge and discharge test was performed at 1C with the charging capacity recorded. The battery was repeatedly charged and discharged from 0V to 0.8V, and the discharge capacity was recorded. The discharge was terminated when the discharge capacity was 60% of the 1C, 0.8V capacity, and the number of cycles was recorded.
[0165] ②2C 0.8V cycle failure parameters (measured at 25℃ and 45℃ respectively):
[0166] The above button battery was discharged at a constant voltage of 0.1V / h to 0.000V, and then charged at 0.1V / h to 0.8V, and the charging capacity was recorded. A button battery was reassembled and a constant current charge and discharge test was performed at 2C with the charging capacity recorded. The battery was repeatedly charged and discharged from 0V to 0.8V, and the discharge capacity was recorded. The discharge was terminated when the discharge capacity was 60% of the gram capacity of 2C and 0.8V, and the number of cycles was recorded.
[0167] The examples 1-9 and comparative examples 1-8 were tested according to the above test method. The test results are shown in Table 3.
[0168] Table 3
[0169]
[0170]
[0171] In Comparative Examples 1-5 and Comparative Example 7, the increase in specific surface area and mesopore specific surface area will increase the silicon content of the obtained silicon-carbon composite material. The improvement in the first efficiency may be because the filling of silicon reduces the appearance of ultramicropores in the porous carbon.
[0172] Compared with Examples 1-9, Comparative Example 6 has a higher first efficiency and a lower lithium insertion expansion, but its 0.8v gram capacity is smaller because the obtained silicon-carbon composite material has a smaller specific surface area and a lower silicon content.
[0173] Compared with Examples 1-9, Example 7 has a higher first efficiency and lower expansion, but its 0.8v gram capacity is only 660mAh / g. This is because its specific surface area is very low, resulting in a lower silicon content in the obtained silicon-carbon composite material, and therefore the overall performance is closer to that of a hard carbon material.
[0174] Compared with Example 6, the specific surface area and silicon content of Comparative Example 8 are smaller, but the development of mesopores is not affected. However, due to its high impurity content, the zinc ion exceeds the standard by a large margin, affecting activation, causing the battery to self-discharge seriously and cycle dive, so the cycle performance is particularly poor.
[0175] In summary, Examples 1-9 use a variety of activation methods to synergistically control the development of porous carbon, reduce costs and increase efficiency, and are more conducive to reducing the production cost of silicon-carbon negative electrodes, so that silicon-carbon negative electrodes can be applied to power batteries rather than being limited to the 3C consumer battery field.
Claims
1. A method for preparing a porous carbon material, characterized in that: It includes the following steps: S1, subjecting a mixture of a carbon material and zinc chloride to heat treatment and acid washing to obtain a first precursor; S2. Mix the first precursor, nitric acid and polar solvent, soak and dry.
2. The method for preparing a porous carbon material according to claim 1, characterized in that: Step S1 satisfies one or more of the following conditions ah: a. The mass ratio of the carbon material to the zinc chloride is 1:(1-10), preferably 1:(3-5); b. The heat treatment temperature is 500-800°C, preferably 600°C; c. The heating rate of the heat treatment is 1-10°C / min, preferably 2°C / min; d. The heat treatment is carried out in an inert atmosphere, and the gas supply rate of the inert atmosphere is 1-10L·kg 1 min -1 , preferably 2L·kg 1 min -1 ; e. The heat treatment holding time is 1-5h, preferably 3h; f. The acid concentration used in the acid washing is 0.1-5M, preferably 1M; g. Particle size D of the carbon material 50 5-10 μm, preferably 8.1 μm; h. The water content of the first precursor is 20%-80%.
3. The method for preparing a porous carbon material according to claim 1, characterized in that: Step S2 satisfies one or more of the following conditions af: a. The pH value of the mixture slurry of the first precursor, nitric acid and a polar solvent is 2-6; b. The polar solvent is one or more of ethanol, N-methylpyrrolidone, water, acetone, ethanol, chloroform, ether, acetic acid, acetonitrile, isopropanol and methanol; c. The amount of the polar solvent is 0.1%-5%, where the percentage is the mass percentage of the polar solvent in the mixture slurry of the first precursor, nitric acid and the polar solvent; d. The soaking time is 5-20h, preferably 10h; e. The immersion pressure is preferably 10-50kPa, for example 10kPa; f. The drying is vacuum drying; wherein the pressure of the vacuum drying is preferably 10-50 kPa; the time of the vacuum drying is preferably 5-20 h; the temperature of the vacuum drying is preferably 80-150°C.
4. The method for preparing a porous carbon material according to claim 1, characterized in that: The product obtained in step S2 is recorded as the second precursor, and after step S2, the following steps are further included: Step S3, performing gas activation treatment on the second precursor; Preferably, step S3 satisfies one or more of the following conditions ad: a. The gas source for the gas activation is CO2; b. The gas activation time is 1-10h; c. The gas activation rate is 0.5-5L·kg 1 min -1 , preferably 2L·kg 1 min -1 ; d. The temperature of the gas activation is 500-800°C, preferably 500-600°C.
5. The method for preparing a porous carbon material according to claim 1, characterized in that: Before step S1, the method further includes: Step S0, carbonizing the mixture containing the carbon source to obtain a carbon material; Preferably, step S0 satisfies one or more of the following conditions ad: a. The carbon source comprises one or more of resin, sucrose, glucose, fructose, starch, cellulose, triglycerides, fatty acids, hemicellulose, lignin and asphalt, preferably a resin, more preferably a phenolic resin; b. The carbonization step further includes a drying step; the drying method is preferably spray drying; c. The carbonization adopts a staged heat treatment; wherein, preferably, the carbonization includes the following stages: The first stage: heating to 50-300℃ at a heating rate of 0.1-20℃ / min, keeping temperature for 5-600min; The second stage: heating to 300-1000℃ at a heating rate of 0.1-20℃ / min, keeping temperature for 5-1200min; d. The carbonization is carried out under an inert atmosphere, which is preferably one or more of nitrogen, helium and argon.
6. A porous carbon material, characterized in that: It is prepared by the method for preparing the porous carbon material according to any one of claims 1 to 5; Preferably, the porous carbon material satisfies one or more of the following conditions ad: a. The specific surface area of the porous carbon material is 1500-2000m 2 / g, for example, 1535m 2 / g、1639m 2 / g, 1867m 2 / g、1693m 2 / g, 1832m 2 / g or 1935m 2 / g; b. The micropore surface area ratio of the porous carbon material is greater than 90%, wherein the micropore surface area ratio refers to the percentage of the specific surface area of the micropores to the total specific surface area of the porous carbon material; c. the mesopore specific surface area of the porous carbon material is less than 10%, for example, 7.0%, 7.7%, 7.9%, 8.0%, 8.1%, 8.4%, 8.8%, 9.3% or 9.8%, wherein the mesopore specific surface area refers to the percentage of the specific surface area of the mesopores to the total specific surface area of the porous carbon material; d. The total pore volume of the porous carbon material is 0.6-1.2cm 3 / g, preferably 1.12cm 3 / g.
7. A method for preparing a silicon-carbon composite material, characterized in that: It includes the following steps: The porous carbon material according to claim 6 is subjected to silicon deposition and carbon coating in sequence.
8. The method for preparing the silicon-carbon composite material according to claim 7, characterized in that: The preparation method satisfies one or more of the following conditions af: a. The silicon source for the silicon deposition comprises silane, wherein the silane preferably comprises one or more of monosilane, disilane, trisilane and butadienesilane; b. The ventilation volume of the silicon source for silicon deposition is 0.1-10L·kg -1 min -1 , for example 0.5L·kg -1 min -1 ; c. During the silicon deposition process, the silicon source and the carrier gas are introduced simultaneously; preferably, the volume ratio of the silicon source to the carrier gas is 1:(2-6), for example, 1:4; d. The temperature of silicon deposition is 400-800° C., for example, 550° C.; e. The silicon deposition time is 3-15h, for example 8h; f. The carbon coating is carried out by vapor deposition; Preferably, the carbon source for carbon coating by vapor deposition method comprises one or more of alkynes, alkanes, olefins, aromatic compounds and carbohydrates; Preferably, the ventilation volume of the carbon source is 0.1-10 L·kg -1 min -1 , for example 2L·kg -1 min -1 ; Preferably, the carbon coating temperature is 300-1000°C, for example 600°C; Preferably, the carbon coating time is 30-1200 min, for example, 600 min.
9. A silicon-carbon composite material, characterized in that: The silicon-carbon composite material is prepared by the method for preparing the silicon-carbon composite material according to claim 7 or 8.
10. Use of the silicon-carbon composite material as claimed in claim 9 as an electrode material in a battery.
Citation Information
Patent Citations
Silicon-carbon composite material as well as preparation method and application thereof
CN116259727A
In-situ porous carbon-nano silicon composite material and preparation method thereof
CN117334880A
Porous carbon, preparation method and preparation system
CN117401674A
Nano silicon-carbon composite material as well as preparation method and application thereof
CN118173733A
Preparation method of high-yield biomass-based sodium ion battery hard carbon negative electrode material
CN118343735A